Penggunaan Classroomscreen dan Google Jamboard untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Peserta Didik di Sekolah Dasar - Astuti, Diana; Sukirwan, Sukirwan; Pamungkas, Aan Subhan; Yandari, Indhira Asih Vivi (SJME (Supremum Journal of Mathematics Education), 2022)
The purpose of this study is to find out the difference in the ability to understand mathematical concepts between students who use classroomscreen media and google jamboard media. The population in this study was a student of class V of SD Negeri Blok C Kota Cilegon Academic Year 2021/2022. The selection of samples by means of total sampling, obtained class V students consisting of V-A as a control class and V-B into an experimental class. The experimental class conducted learning with classroomscreen media, while the control class did learning with google jamboard media. Data retrieval is obtained by test methods to determine the ability to understand the mathematical concepts which are then analyzed with average difference tests. The result of the research obtained is the ability to understand the mathematical concepts of experimental class better than the ability to understand the mathematical concepts of control class.